Crescimento de raízes de soja em resposta a variações químicas, físicas e biológicas do solo - Müller, Mariele (2020)
Environmental conditions affect agricultural production, and water deficit has been highlighted by the negative impact on soybean production. Thus, radicial growth in greater volume and depth can be an alternative to minimize losses caused by lack of water. Knowledge of how soybean roots behave in view of soil chemical, physical and biological attributes can help establish managements that benefit root growth in depth. The objective was to evaluate the growth of soybean roots in response to chemical, physical, and biological variations in the soil, in different soil locations and depths. Six experiments were carried out in different locations. Soil samples were collected every 5 cm to 60 cm depth for chemical, physical and biological analysis of the soil. The roots were collected every 5 cm deep up to 45 cm deep in the soil. The chemical attributes of the evaluated soil correspond to the complete standard laboratory analysis. The physical attributes evaluated were relative density, soil porosity and resistance to root penetration. Biological attributes were microbial biomass, baseline respiration and metabolic quotient. From the roots, roots, length, surface, diameter, volume, dry matter, and fine, medium, and coarse root were determined. The six sites presented unsatisfactory values of pH and organic matter and presented phosphorus, potassium and calcium concentrated in the first centimeters of soil depth. The total porosity of the soil was higher than 50 m3/m3, but the proportion of macropores, micropores and cryptopores resulted in soils with resistance to penetration to the roots. Microbial biomass was higher on the soil surface when compared to deeper soil layers, however, the metabolic quotient was higher in depth, showing that microorganisms in depth have low capacity to incorporate carbon into microbial biomass. Radical growth occurred in a greater proportion on the soil surface, possibly because the soil attributes that favor root growth are concentrated at this time.